The Effect of Economic Value Added, Financial Value Added, and Market Value Added on Stock Returns (Case Study of the Technology Sector Listed on the IDX for the 2021-2024 Period) - Muhammad Taufik Rahman; Dede Hertina (International Journal of Marketing & Human Resource Research, 2026)
This study examines the effect of value-based performance measures, namely Economic Value Added (EVA), Financial Value Added (FVA), and Market Value Added (MVA), on stock returns of technology sector firms listed on the Indonesia Stock Exchange over the 2021–2024 period. The motivation of this study arises from the growing dominance of technology firms in capital markets, where traditional accounting-based performance indicators are increasingly questioned due to high innovation intensity, reliance on intangible assets, and volatile valuation dynamics. Using a quantitative explanatory approach, this study analyzes panel data comprising 17 technology firms, yielding 68 firm-year observations. The empirical analysis employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the relationships between value-based performance indicators and stock returns. EVA, FVA, and MVA are used as proxies for firm-level value creation, while stock return represents market-based performance. The empirical results reveal that none of the proposed hypotheses is statistically supported. EVA shows a positive but insignificant association with stock returns, whereas FVA and MVA exhibit negative, insignificant effects. Furthermore, the model demonstrates extremely low explanatory and predictive power, indicating that value-based performance measures explain only a negligible portion of stock return variation in the technology sector. These findings suggest that stock returns of technology firms are largely driven by factors beyond accounting- and value-based performance indicators, such as investor sentiment, growth expectations, and market narratives. The study contributes to the literature by highlighting the limited ability of traditional value-based metrics to explain short-term stock returns in technology-intensive industries, particularly in emerging markets. Practical implications are provided for managers and investors in aligning performance evaluation and investment decisions with sector-specific characteristics.